2019
DOI: 10.3390/e21100973
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Production Rates of the Multi-Dimensional Fractional Diffusion Processes

Abstract: Our starting point is the n-dimensional time-space-fractional partial differential equation (PDE) with the Caputo time-fractional derivative of order β , 0 < β < 2 and the fractional spatial derivative (fractional Laplacian) of order α , 0 < α ≤ 2 . For this equation, we first derive some integral representations of the fundamental solution and then discuss its important properties including scaling invariants and non-negativity. The time-space-fractional PDE governs a fractional diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Furthermore, the entropy production rate of the quasidiffusion propagator in the one-dimensional and two-dimensional cases is the same as for Gaussian diffusion process [48][49][50]. However, in the one-dimensional case, the second spatial moment of the probability density function, P 1 (x, t), does not exist and the mean squared displacement of the diffusing particles is not finite, indicating the diffusion process is anomalous [48][49][50]. Similarly, for the two-dimensional case, the second moment of P 2 (x, t), does not exist for 0.5 < α ≤ 1 and the diffusion is anomalous with long-tailed waiting time and jump lengths.…”
Section: The Quasi-diffusion Propagatormentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the entropy production rate of the quasidiffusion propagator in the one-dimensional and two-dimensional cases is the same as for Gaussian diffusion process [48][49][50]. However, in the one-dimensional case, the second spatial moment of the probability density function, P 1 (x, t), does not exist and the mean squared displacement of the diffusing particles is not finite, indicating the diffusion process is anomalous [48][49][50]. Similarly, for the two-dimensional case, the second moment of P 2 (x, t), does not exist for 0.5 < α ≤ 1 and the diffusion is anomalous with long-tailed waiting time and jump lengths.…”
Section: The Quasi-diffusion Propagatormentioning
confidence: 99%
“…Several interesting mathematical results have been derived from the Green's function in the special case of the CTRW model for 2α/β = 1. It has been shown that the oneand two-dimensional quasi-diffusion propagators are probability density functions that evolve spatially in time [48][49][50]. Furthermore, the entropy production rate of the quasidiffusion propagator in the one-dimensional and two-dimensional cases is the same as for Gaussian diffusion process [48][49][50].…”
Section: The Quasi-diffusion Propagatormentioning
confidence: 99%
See 2 more Smart Citations
“…The manuscript “Entropy Production Rates of the Multi-Dimensional Fractional Diffusion Processes”, by Yuri Luchko, derives and analyzes the fundamental solution to the n -dimensional time-space-fractional partial differential equation with the Caputo time-fractional derivative of order b , , and the fractional spatial derivative (fractional Laplacian) of order a , . An explicit formula for the entropy production rate of the fractional diffusion processes is presented [ 10 ].…”
mentioning
confidence: 99%